A General Model for Railway Systems Risk Assessment with the Use of Railway Accident Scenarios Analysis. (2017) - Leitner, Bohus
Abstract: The paper shows the developing process of the railway system risk assessment models and the indication of their applicability to the Slovakian railways. The risk assessment models are based on the accident scenarios. Various hazardous events, which have the potential to lead directly to casualties, were defined by gathering various accident reports and having workshops with railway safety experts. The developed models will be used to assess the accident risk of the Slovak railway system. The frequency of each hazardous event was evaluated from the historical accident data and structured expert judgments by using the FTA technique, ETA technique and other safety techniques were applied.